Hochschullernwerkstätten - Elemente von Hochschulentwicklung? Ein Rückblick auf 15 Jahre Hochschullernwerkstatt in Halle und andernorts - Kramer, Kathrin; Rumpf, Dietlinde; Schöps, Miriam; Winter, Stephanie (Lernen und Studieren in Lernwerkstätten, 2020)
One claim of learning workshops is to participate in the development of the respective institution. This volume shows the importance of higher education learning workshops for the shaping of higher education landscape(s) and focuses on five topics: What historical developments can be identified? What shapes the self-understandings in higher education learning workshops? How can colleges and universities participate in processes of inclusion/exclusion in higher education learning workshops? What specific perspectives become apparent in relation to professionalisation and reflection? To what extent can cooperation and cooperative learning within university learning workshops be transferred to other university areas?